(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to examine the impact of the Carousel strategy on deep comprehension among second-grade middle school students in physics. To achieve this objective, the researchers employed an experimental approach with two groups (experimental and control), each partially controlling the other, utilizing a post-test design to assess deep comprehension. The research population comprised second-grade middle school students attending government daytime schools for boys in the Al-Karkh Third Directorate of Education, Baghdad, during the academic year (2023-2024). Al-Rawad Boys Secondary School was intentionally selected to represent the current research sample, consisting of (70) students, with (35) students allocated to the experimental group and (35) to the control group. The scientific subject taught to both research groups encompassed the first three chapters of the physics textbook. A deep comprehension test comprising (20) items was developed, and psychometric properties and statistical analysis were conducted to determine difficulty, discrimination, and the effectiveness of alternatives. Following the conclusion of the experiment, the researcher administered the test, revealing a statistically significant difference in deep comprehension between the experimental and control groups, favoring the experimental group.